Appendicular lump: comparative study of immediate surgical versus conservative management - Agarwal, Vimal K.; Agrawal, Sonal (International Surgery Journal, 2017)
Background: At present acute appendicitis is leading cause of acute surgical abdomen. Treatment of choice for non-complicated appendicitis is appendicectomy. Delayed presentation of appendicitis cause lump formation in 2-6% case. Traditional treatment of appendicular lump is conservative treatment followed by interval appendicectomy. Our study was done to make a better management plan for lump patients. Methods: In this retrospective study 52 patients having appendicular lump randomly divided in two group, Group 1 conservative treatment followed by interval appendicectomy after 6-8 weeks and group 2 immediate surgery. Highest incidence of appendicular lump was found in age group of 21-30 year. Average hospital stay in group 1 was 12 days as compare to 4 day in group 2. Results: Immediate surgery in our study suggest better management plan for appendicular lump in term of less hospital stay, less economic burden, no need of readmission in hospital and no major complication. Conclusions: Early exploration for appendicular lump is preferred option rather than conservative treatment followed by interval appendicectomy.